New Approaches in the Treatment of Covid-19 Virus - Ataie Amin; Ataee Ramin (Journal of Current Viruses and Treatment Methodologies, 2020)
By increase the incidence of infection of coronavirus disease 2019 (COVID-19), diagnostic factors for early identification of high-risk individuals are important. On the other hand, more infections are in older patient, comorbidities, and male patients. Identification of components that related to severity of COVID-19 contributed to ACE2 and TMPRSS2 genes, which are critical for viral infection. It was found that adding enzyme copy, hrsACE2, lures the virus to attach itself to it instead of the actual cells… It inhibits the virus from infecting the cells in the lungs and other organs.
Keywords: Covid-19